Characterisation of Microbial Property of Polyvinyl Alcohol Hydrogel Synthesised via Crosslinking Method with Incorporation of Freeze-Dried Snail Mucin - Kuan Tyng Yih,; Aliff Hisyam Bin A Razak,; Rama Yusvana, (Progress in Engineering Application and Technology, 2025)
This study focuses on the development and optimization of polyvinyl alcohol (PVA) hydrogels incorporated with freeze-dried snail mucin, aiming to enhance their performance for wound healing applications. PVA hydrogels were synthesized using a freeze-thaw crosslinking method, and snail mucin was integrated to improve bioactivity, water absorption, adhesion, and mechanical strength. The optimization process, utilizing Response Surface Methodology (RSM), identified the ideal conditions for maximum water absorption and adhesion as 35% PVA, 3.81% snail mucin, and an 18-hour freezing time. The hydrogels exhibited significantly improved water retention, tensile strength, and hydrophilicity compared to pure PVA hydrogels. Fourier Transform Infrared Spectroscopy (FTIR) and Scanning Electron Microscopy (SEM) confirmed successful incorporation of snail mucin and highlighted the formation of a porous structure in the mucin-loaded hydrogels. While antimicrobial testing showed limited efficacy, the hydrogels demonstrated promising mechanical and functional properties for wound care, making them potential candidates for future biomedical applications. Future work will focus on enhancing antimicrobial activity and further optimizing the hydrogels for clinical use.